1995
DOI: 10.3758/bf03213065
|View full text |Cite
|
Sign up to set email alerts
|

Misalignment effects in 3-D versions of Poggendorff displays

Abstract: Strong misalignment effects are found in three-dimensional (3-D)versions of Poggendorff displays viewed binocularly. The components of the standard 2-D Poggendorff figure-the parallels and the oblique segments-were presented in 3-Ddepth as a flat rectangular object with occluding edges and an oblique line situated behind the object. Three experiments investigated the misalignment effects under three different observation instructions: Subjects were told to look at the oblique (Experiment 1), at the rectangle (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The studies reported in the literature, however, show that these two possible consequences are limited to visual direction and do not occur for visual shape and visual alignment in 3-D perception (Ohtsuka and Yano 1994;Ono et al 1998;van Ee and Erkelens 2000). In 3-D space a square behind an occluder is seen as a square (Ohtsuka 1995a;Ono et al 1998) and a line behind an occluder is seen aligned (Liu and Kennedy 1995;Ohtsuka 1995b;Drobnis and Lawson 1976;Gyoba 1978). To demonstrate for yourself that the expectations illustrated in figure 7B do not occur, see demonstration 5 on the website.…”
Section: 22mentioning
confidence: 99%
“…The studies reported in the literature, however, show that these two possible consequences are limited to visual direction and do not occur for visual shape and visual alignment in 3-D perception (Ohtsuka and Yano 1994;Ono et al 1998;van Ee and Erkelens 2000). In 3-D space a square behind an occluder is seen as a square (Ohtsuka 1995a;Ono et al 1998) and a line behind an occluder is seen aligned (Liu and Kennedy 1995;Ohtsuka 1995b;Drobnis and Lawson 1976;Gyoba 1978). To demonstrate for yourself that the expectations illustrated in figure 7B do not occur, see demonstration 5 on the website.…”
Section: 22mentioning
confidence: 99%
“…sion with 3 -dimensional stimuli depends upon the actual distance between the oblique and the inducing element (Liu & Kennedy, 1995). Thus, it would be interesting to compare sex differences in 2-dimensional and 3-dimension-a1 Poggendorff contexts to identify whether sex differences would be reduced in the latter context, one in which depth information is directly available to the participants.…”
mentioning
confidence: 99%
“…It is similar to Gregory's (1963) hypothesis about the inappropriate constancy scaling as an explanation for the Mueller-Lyer illusion (see Day & Knuth, 1982;Robinson, 1972). Moreover, the ideas presented here address theoretical puzzles, namely, (a) why shape perception remains veridical in three-dimensional perceptual space despite visual direction being nonveridical (Ohtsuka & Ono, 2002;van Ee & Erkelens, 2000); (b) why in three-dimensional perceptual space, a square behind an occluder is seen as a square (Ohtsuka, 1995a;Ono et al, 1998) and an oblique line behind an occluder is seen aligned (Drobnis & Lawson, 1976;Gyoba, 1978;Liu & Kennedy, 1995;Ohtsuka, 1995b); and (c) why the end of an oblique line that abuts an occluder in a drawing appears more misaligned than does its far end (Wenderoth, 1980). To propose that the underlying mechanism for visual direction examined in this study is different from that for shape and alignment is plausible but ad hoc.…”
Section: Discussionmentioning
confidence: 99%